Adoção de artefatos gerenciais: um estudo empírico a partir da teoria da contingência no âmbito de empresas do setor hoteleiro de João Pessoa - Dutra, Adília Ribeiro Coutinho Suassuna (2019)
This study was to analyze the relations between contingency factors and the use of management tools within the hotel chain. To reach the proposed objective realized, a descriptive, exploratory and quantitative research. The universe understood all 106 companies listed in the registry of the Municipal Secretariat of Tourism of the city of João Pessoa, of which 98 accepted to participate in this research. Data collection was performed through face-to-face interviews with the manager of the management sector, in July and August 2018. Statistical procedures related to descriptive statistics and Spearman's correlation were performed using the STATISTICA system. The most commonly used traditional management artifacts on budget, budget analysis and traditional costing techniques were obtained as preponderant results. In relation to the modern management tools, the frequency of use of the artifacts on life cycle analysis and just in time for decision making in the long term was emphasized. It has been realized that a managerial artifact used in one organization may not have the same success in another. The investigated companies pointed out as very important the contingency factors related to competence for labor, to customer satisfaction, to invest in technological innovation, to use integral software, to ecommerce as an effective way to sell the lodging and to cherish high quality in the provision of services. When correlating the statistical significance of the relationships between the contingency factors: environment and the use of modern artifacts, there were low correlation indices presenting negatively activity-based costing and competition attitudes. It is also worth noting that in the scope of the companies participating in the research, there was flexibility to change or improve the managerial tools used, without resistance to change, which is a positive point.